Gallic acid: a dietary metabolite’s therapeutic potential in the management of atherosclerotic cardiovascular disease - Zhao, Xiao-Lan; Cao, Zhang-Jing; Li, Ke-Di; Tang, Fei; Xu, Li-Yue; Zhang, Jing-Nan; Liu, Dong; Peng, Cheng; Ao, Hui (Frontiers in Pharmacology, 2025)
Atherosclerotic cardiovascular disease (ASCVD) causes significant morbidity and mortality globally. Most of the chemicals specifically target certain pathways and minimally impact other diseases associated with ASCVD. Moreover, interactions of these drugs can cause toxic reactions. Consequently, the exploration of multi-targeted and safe medications for treating and preventing ASCVD has become an increasingly popular trend. Gallic acid (GA), a natural secondary metabolite found in various fruits, plants, and nuts, has demonstrated potentials in preventing and treating ASCVD, in addition to its known antioxidant and anti-inflammatory effects. It alleviates the entire process of atherosclerosis (AS) by reducing oxidative stress, improving endothelial dysfunction, and inhibiting platelet activation and aggregation. Additionally, GA can treat ASCVD-related diseases, such as coronary heart disease (CHD) and cerebral ischemia. However, the pharmacological actions of GA in the prevention and treatment of ASCVD have not been comprehensively reviewed, which limits its clinical development. This review primarily summarizes the in vitro and in vivo pharmacological actions of GA on the related risk factors of ASCVD, AS, and ASCVD. Additionally, it provides a comprehensive overview of the toxicity, extraction, synthesis, pharmacokinetics, and pharmaceutics of GA,aimed to enhance understanding of its clinical applications and further research and development.